GAMBARAN KEPATUHAN HAND HYGIENE PADA MAHASISWA PROGRAM PROFESI NERS DI RSUD ULIN BANJARMASIN - Romdoni, Muhammad Akbar; Rahmiati, Rahmiati; Mulyani, Nina; Wibowo, Agung Ary; Muthmainah, Noor (Homeostasis, 2023)
Healthcare Associated Infections (HAIs) are infections in patients acquired in hospitals which are strongly influenced by the cleanliness of nursing students who are practicing at the hospital. Nurse student hand hygiene compliance is a fundamental behavior in an effort to prevent HAIs. The purpose of this study was to find out the compliance of hand hygiene among nursing students at Ulin Hospital, Banjarmasin. This study used an observational survey method with 15 samples. The results of this study indicate the compliance of nurse students with five moments hand hygiene 85%, which 75% adhered to the procedure . Based on gender, female 90.6% and male 78.6%. Based on the five moments indication, after exposure to body fluids 100%, after touching the patient 100%. before touching the patient 80%, before aseptic action 60%, %. The conclusion of this study is that most nursing students perform hand hygiene at five moments, the compliance of female is higher than men, the highest adherence is found after exposure to body fluids and after touching the patient while the lowest compliance is found at before the aseptic procedure and most of the nursing students perform.